2020
DOI: 10.1186/s12916-020-01855-9
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity, metabolites, and colorectal cancer risk: Mendelian randomization study

Abstract: Background Higher adiposity increases the risk of colorectal cancer (CRC), but whether this relationship varies by anatomical sub-site or by sex is unclear. Further, the metabolic alterations mediating the effects of adiposity on CRC are not fully understood. Methods We examined sex- and site-specific associations of adiposity with CRC risk and whether adiposity-associated metabolites explain the associations of adiposity with CRC. Genetic variants… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 72 publications
1
68
0
Order By: Relevance
“…Gender difference was nevertheless significant only in colorectal cancer. This finding is supported by a Mendelian randomization study [7] on the association between BMI and colorectal cancer incidence: risk was 22% higher among men per 4.2 kg/m 2 increase in BMI and 9% higher among women per 5.2 kg/m 2 . In 2016, the International Agency for Research on Cancer (IARC) Working Group added hepatocellular carcinoma, meningioma, gastric cardia and ovarian cancers to the aforementioned obesity-associated tumors [8].…”
Section: Incidence: When Obesity Promotes Cancermentioning
confidence: 52%
“…Gender difference was nevertheless significant only in colorectal cancer. This finding is supported by a Mendelian randomization study [7] on the association between BMI and colorectal cancer incidence: risk was 22% higher among men per 4.2 kg/m 2 increase in BMI and 9% higher among women per 5.2 kg/m 2 . In 2016, the International Agency for Research on Cancer (IARC) Working Group added hepatocellular carcinoma, meningioma, gastric cardia and ovarian cancers to the aforementioned obesity-associated tumors [8].…”
Section: Incidence: When Obesity Promotes Cancermentioning
confidence: 52%
“…A question, therefore, emerges whether excess abdominal fat mediates the development of cancers associated with abdominal obesity 39 , or abdominal obesity and cancer are parallel outcomes with shared genetic predisposition. Although studies exploring a causal relationship between body shape and cancer are limited, Mendelian randomisation based on traditional body-shape indices has already provided evidence for causal positive associations of WHR or WHR adj BMI with colorectal cancer 40 , 41 and renal cell carcinoma 42 but an inverse association with breast cancer 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a Mendelian randomization study revealed that higher BMI was associated with increased CRC risk only in men, whereas a higher WHR was more closely correlated with CRC risk in women than in men [ 122 ]. WC, not BMI, was also positively related to CRC risk in postmenopausal women, which might be associated with VAT accumulation [ 123 ].…”
Section: Sex Differences In the Incidence Of Major Gastrointestinamentioning
confidence: 99%